2010
DOI: 10.1038/sj.bjc.6605639
|View full text |Cite
|
Sign up to set email alerts
|

Age of mother and grandmother in relation to a subject's breast cancer risk

Abstract: BACKGROUND: On theoretical grounds, the age of the grandmother and the age of the mother at delivery of her daughter may affect the breast cancer risk of the granddaughter. METHODS: We used the data relating to the Diagnostic Research Mamma-carcinoma cohort (DOM (Diagnostisch Onderzoek Mammacarcinoom) 3), which comprises a population-based sample of 12 178 women aged 41 -63 years at enrolment in 1982 -85 and followed up until 2000. During follow-up 340 postmenopausal breast cancer cases were identified. To the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Negative association has also been detected in testicular cancer for children of higher birth order [ 4 - 6 ]. Higher birth order often implies higher parental age at conception, although the latter has not been reported to be a risk factor in some studies [ 7 , 8 ] whereas in other studies there was an association found for cancer sites as breast and prostate cancer as well as childhood cancers [ 9 - 13 ]. Genetic diseases or cancer during childhood may shorten the reproduction phase of parents, which could cause higher risk for individuals in families with fewer children [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Negative association has also been detected in testicular cancer for children of higher birth order [ 4 - 6 ]. Higher birth order often implies higher parental age at conception, although the latter has not been reported to be a risk factor in some studies [ 7 , 8 ] whereas in other studies there was an association found for cancer sites as breast and prostate cancer as well as childhood cancers [ 9 - 13 ]. Genetic diseases or cancer during childhood may shorten the reproduction phase of parents, which could cause higher risk for individuals in families with fewer children [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are only aware of a few examples in human and some animals studied in laboratory conditions. In human medicine, it has been shown that GM age is a risk factor for trisomy 21 (Papp et al, 1977;Aagesen et al, 1984;Malini & Ramachandra, 2006, but see also, Allen et al, 2009;Kovaleva et al, 2010) but not for breast cancer (de Haan et al, 2010) and that grandpaternal age is positively correlated with telomere size in grandoffspring (Eisenberg et al, 2012(Eisenberg et al, , 2019. In non-human animals, the pioneering study in rotifers (Lansing, 1947) showed that the repeated effects of the same maternal age over multiple generations increasingly influenced grandoffspring lifespan, i.e., with evidence of a cumulative effect over multiple generations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was determined in the study conducted by Haan et al that the age of the mother or grandmother did not play an important role in the breast cancer risk of her daughter or granddaughter (Haan et al, 2010).…”
mentioning
confidence: 99%